Faktor-Faktor yang Memengaruhi Pengelolaan Aset Pemerintah - Harfianah, Sukaena; Faisal, Faisal (E-Jurnal Akuntansi, 2023)
Efficient and effective asset management is considered very important in improving the quality of financial reports and state financial management. This research aims to determine the influence of human resources, information technology and governance on government asset management at the Central Statistics Agency of the Republic of Indonesia (BPS). This research uses multiple linear regression analysis methods to test the data. The sampling technique used was a systematic random sampling method which resulted in a sample size of 260. The survey was carried out using a Google form. Data processing uses the SPSS 25 program. The research results show that human resource variables have no effect on government asset management, while information technology and governance have a positive and significant effect on government asset management. Keywords: Human Resources; Information Technology; Good Governance; Government Asset